(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the efficacy of balloon tamponade in controlling PPH. Study Design: Descriptive cross sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, GKMC Swabi from January 2023 to June 2023. Methods: A total of 134 patients were included in the study. Information regarding age, gestational age, mode of delivery, assessment of effective bleeding was recorded. Effectiveness was measured if the bleeding stops within 15 minutes of applying tamponade, and if no bleeding occurred within 24 hours and after removing of balloon tamponade. Blood loss estimation sanitary pad was weighed beforehand and after being soaked in blood was weighed again and difference was noted, 1 gm was taken as 1ml. All the data was analyzed by using SPSS. Results: This study was conducted on 134 patients. The Mean and SD for age was 26.69±4.21. Mean and SD for gestational week was 38.51±1.102. Mean and SD for parity was 2.04±2.11. Mean and SD for blood loss in mL was 896.34±186.72. The mode of delivery in 126 (94%) patients was spontaneous and in 8 (6%) patients it was instrumental. Balloon tamponade was found effective in 127 (94.8%) patients and was not found effective in 7 (5.2%) patients. Conclusion: We conclude that the use of condom balloon tamponade can effectively help in reducing blood loss and both maternal morbidity and mortality associated with PPH.